Assembly of pericellular matrices by COS-7 cells transfected with CD44 lymphocyte-homing receptor genes. - Knudson, W (1993)
The capacity to assemble and retain a pericellular matrix is correlated with the expression of the cell surface binding sites specific for the extracellular matrix macromolecule hyaluronan. These binding proteins have been termed hyaluronan receptors. The lymphocyte-homing receptor CD44 may have identity with these hyaluronan receptors. To determine whether hyaluronan receptors function independently in this capacity for matrix assembly, mammalian cells were transfected with cDNA encoding the putative hyaluronan receptor CD44. After transfection with CD44 cDNA, COS cells gained the capacity to assemble hyaluronan-dependent pericellular matrices in the presence of exogenously added hyaluronan and proteoglycan. Thus, CD44 receptors do function as matrix-organizing, matrix-anchoring hyaluronan-binding proteins. In addition, the expression of CD44/hyaluronan receptors alone is sufficient to direct this matrix assembly. If matrix assembly is a function of cells in vivo that express hyaluronan receptors, this raises interesting possibilities for the role of the receptors in cell migration, when new extracellular matrix environments are encountered.